UTILIZATION OF LIGNIN ISOLATION RESULTS FROM OIL PALM FRONDS AS ADHESIVE IN COMPOSITE BOARD PREPARATION - Silitonga, Nelson; Kartika; Abdillah; Syarifah; Keliat, Aisyah Br.; Arif, Ali; Purwandari, Vivi; Saragih, Gimelliya (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2024)
The decreasing availability of adhesive raw materials and the emergence of formaldehyde emissions from gluing material products to the environment, require a substitute material in the manufacture. Lignin from oil palm fronds has the potential as an alternative environmentally friendly adhesive in the composite board industry and offers a sustainable agricultural waste management solution because of its abundant availability. This study is a laboratory experiment, the utilization of lignin from oil palm fronds, which will later be applied as a composite wood adhesive. From the results of the study obtained. copolymerization with resorcinol and formaldehyde produces lignin resorcinol formaldehyde (LRF) resin which is tested for adhesive appearance, pH/acidity, specific gravity, and viscosity of LRF adhesive at room temperature and residual evaporation levels at 105 oC. Product characterization includes testing the physical and mechanical properties of composite boards including Fracture Strength (Modulus of Rufture) and Flexural Strength or Modulus of Elasticity (MOE) from the test results of this lignin-based adhesive which meets the specified requirements.